Disparities in Reproductive Aging and Midlife Health between Black and White women: The Study of Women's Health Across the Nation (SWAN) - Siobán D. Harlow; Sherri-Ann M. B; Gail A. Greendale; Nancy E. Avis; Alexis N. Reeves; Thomas R. Richards; Tené T. Lewis (BMC, 2022)
Abstract This paper reviews differences in the experience of the menopause transition and midlife health outcomes between Black and White women who participated in the Study of Women's Health Across the Nation (SWAN), a 25-year, longitudinal, multi-racial/ethnic cohort study. We identify health disparities, i.e., instances in which Black women's outcomes are less favorable than those of White women, and consider whether structural racism may underlie these disparities. Although SWAN did not explicitly assess structural racism, Black women in SWAN grew up during the Jim Crow era in the United States, during which time racism was legally sanctioned. We consider how we might gain insight into structural racism by examining proxy exposures such as socioeconomic characteristics, reports of everyday discrimination, and a range of life stressors, which likely reflect the longstanding, pervasive and persistent inequities that have roots in systemic racism in the US. Thus, this paper reviews the presence, magnitude, and longitudinal patterns of racial disparities observed in SWAN in six areas of women's health - menopause symptoms, sleep, mental health, health related quality of life, cardio-metabolic health, and physical function -and elucidates the contextual factors that are likely influencing these disparities. We review the strengths and weaknesses of SWAN's design and approach to analysis of racial disparities and use this as a springboard to offer recommendations for future cohort studies.